Patent mining on soil pollution remediation technology from the perspective of technological trajectory. (1st January 2023) - Qi, Zefeng; Han, Yixin; Afrane, Sandylove; Liu, Xi; Zhang, Mingqi; Crittenden, John; Chen, Jian Lin; Mao, Guozhu
Abstract: Recent years have seen a marked growth in soil environmental problems, however, the research & development (R&D) direction of soil pollution remediation technology (SPRT) for addressing related challenges to the global ecosystem is still unclear. Patent is the most effective carrier of technological information. Therefore, this study investigates the status and future direction of SPRT through the analysis and mining of 14, 475 patents from 1971 to 2020. In 2006–2020, 14, 435 SPRT patents (79% of the total) were published, which is in the development stage. By measuring the proportion of high-value patents, determined by the ratio of the number of patent families containing two or more patents (PF2) to that containing at least one patent (PF1), we found that United States (PF2/PF1 = 0.711), Japan (PF2/PF1 = 0.500), and South Korea (PF2/PF1 = 0.431) hold a monopoly. International patent organizations serve as a bridge for technology transfer. Patent CN101947539-A measured by structural hole index (Effective size = 98.194, Efficiency = 0.926) has the most significant technological influence. Therefore, in order to accomplish the technological transition and improve the soil remediation capacity, more attention should be paid to the microbial-assisted phytoremediation technology related to inorganic pollutants, hyperaccumulators and stabilizers. Additionally, patents CN102834190-A (Effective size = 23.930, Efficiency = 0.855, Constraint = 0.141, Hierarchy = 0.089) and CN105855289 (Effective size = 21.453, Efficiency = 0.795 Constraint = 0.149, Hierarchy = 0.086) are both at the location of structural holes. So, more research should be carried out on green and cost-effective solutions for reducing organic pollutants in soil remediation. The current study identifies opportunities for innovations and breakthroughs in SPRT and offers relevant information on technological development prospects. Graphical abstract: Image 1 Highlights: 14, 475 patents on SPRT were evaluated through patent analysis. The technology transfer of SPRT tends to monopolize. Pollutants, sources, remediation technologies and equipment are core patents. Dynamic technology trajectory of SPRT were firstly studied. Efficient and green remediation technology is the innovative direction of SPRT.